2011
DOI: 10.1186/1471-2121-12-48
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II activity dependent and independent vinculin recruitment to the sites of E-cadherin-mediated cell-cell adhesion

Abstract: BackgroundMaintaining proper adhesion between neighboring cells depends on the ability of cells to mechanically respond to tension at cell-cell junctions through the actin cytoskeleton. Thus, identifying the molecules involved in responding to cell tension would provide insight into the maintenance, regulation, and breakdown of cell-cell junctions during various biological processes. Vinculin, an actin-binding protein that associates with the cadherin complex, is recruited to cell-cell contacts under increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Force-induced conformation changes within the cadherin/catenin complex could elicit downstream signaling, for example, by modulating binding affinity to direct or indirect binding partners such as EPLIN or vinculin (17-21, 25, 27-29). Protein accumulation at adhesion sites could thus promote changes in cell and tissue mechanical properties and cell adhesive and migratory behavior (18,25,26,28,29). Over longer timescales, this may also regulate gene expression and likewise have important roles during development and disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Force-induced conformation changes within the cadherin/catenin complex could elicit downstream signaling, for example, by modulating binding affinity to direct or indirect binding partners such as EPLIN or vinculin (17-21, 25, 27-29). Protein accumulation at adhesion sites could thus promote changes in cell and tissue mechanical properties and cell adhesive and migratory behavior (18,25,26,28,29). Over longer timescales, this may also regulate gene expression and likewise have important roles during development and disease.…”
Section: Discussionmentioning
confidence: 99%
“…External forces applied to cells through cadherins reveal a mechanical coupling between the membrane and the cytoskeleton that requires the cadherin cytoplasmic domain (24) and may cause changes in cellular mechanical properties or protrusive activity (25,26). Conformational changes in α-catenin and/or the recruitment of cytoskeleton-binding proteins to sites of cadherin-mediated adhesion may be involved (17,18,(27)(28)(29). However, there is no direct evidence at the molecular level that cadherins are under actomyosin-dependent tension or that cadherins transmit extracellular forces to the cytoskeleton through the catenin-binding cytoplasmic domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been shown that vinculin can localize to apical cell-cell junctions in a force-dependent and force-independent manner. The latter is mediated by an increased stabilization of F-actin, and could thus rely on the actin-binding activity of vinculin, rather than on its interaction with a-catenin (Sumida et al, 2011). EPLIN also localizes to the actin cytoskeleton outside of cell-cell junctions [ (Abe and Takeichi, 2008;Song et al, 2002) and our unpublished observations].…”
Section: Box 1 A-catenin Vinculin and Their Interaction Partners -Amentioning
confidence: 99%
“…Interestingly, however, vinculin localization was minimal at self-contacts ( Fig. S9 and Movie S7), suggesting that self-contacts are relatively force-free, although vinculin accumulation does not necessarily correlate with myosin activity in MDCK cells (29).…”
Section: Discussionmentioning
confidence: 97%